(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article discusses the issues of the rational use of antimicrobial agents, the study of the structure of the use of these agents in the pharmacotherapy of community-acquired pneumonia in children, and the study of mistakes made by doctors when choosing a rational antimicrobial agent. Also, antimicrobial agents used to treat pneumonia in children will be considered, as well as their dosage regimens and methods of administration are presented.